Acceptance of WeChat Pay among Consumers in Malaysia - Chua, Jia Jia; Wang, Annie, Pei Ling (INTI International University, 2019)
WeChat, the most popular social media application in China, had recently launched its integrated mobile payment feature, WeChat Pay, in Malaysia. With the advancement of technology, mobile payment potentially become a replacement to cash, cheques, credit cards and debit cards. However, Bank Negara Malaysia reported that, in 2017, the mobile payment transaction value per capita is only RM0.50 which is far lesser than cash transaction at RM2,881.40 per capita. Therefore, this study intends to determine the acceptance of WeChat Pay, and identify the factors influencing the acceptance among consumers in Malaysia. The findings show that, perceived ease of use, perceived usefulness and perceived risk have a significant relationship with the acceptance of WeChat Pay among consumers in Malaysia.